Penerapan Marketing Mix dan Pelabelan Proll Tape Dalam Peningkatan Santripreneur Pondok Modern Al-Ghuroba Sorong - Maulin Adinda; Nadia Rafni Ramadina; Intan Cindika Ananta; Cahyanti Cahyanti; Vicky Shanaz Nurul Fajrin; Susetyowati Sofia; Agilistya Rahayu; Dwi Iin Kahinah (Jurnal Pengabdian Masyarakat, 2023)
Marketing strategy has a very important role for business success. As an effort to help creative products go public. Having limited insight into marketing, the team provides assistance to market the results of creativity in the community of female students and religious teachers who serve at Pondok Modern Al-Ghuroba. Training activities for participants were carried out on Saturday, October 14 2023. Pondok Modern Al-Ghuroba Sorong, whose address is Jl. Flamboyant Klasuluk Village, Mariat District, Sorong Regency. The service activity method is carried out using the following steps: 1). preparation stage, 2). program socialization stage, 3). program implementation stage, 4). program assistance stage, 5). monitoring stage, 6). implementation evaluation. Training activities can be described as follows: 1). training on how to manage the production of tape into sponge cake proll tape, 3). training on the production preparation process, production process to packaging and labeling, 3). training on marketing processes, marketing models, marketing ethics , tips, tricks for success in marketing, 4). discussion about the advantages and obstacles in the business world. Training activities have been carried out to provide creativity and skills to female students and ustazah regarding processing tape into processed food, namely cake proll tape. Reinforcement of material and discussion with participants regarding training, marketing management and entrepreneurial motivation as well as assistance in carrying out production, packaging, label design and labeling processes.